Atomistic Model Approach to Identify Defects, Lithium Ion Diffusion and Trivalent Dopants in Li2MnO2 - Kuganathan, N.; Sashikesh, G.; Abiman, P.; Chroneos, A. (Jaffna Science Association, 2019)
Layered lithium-rich metal oxides have attracted great interest as potential cathode materials for Li ion batteries due to their high Li content required for high energy density. Using atomistic simulation techniques based on classical pair potentials, we calculate intrinsic defects, lithium ion diffusion paths together with activation energies and trivalent doping in Li2MnO2. The most favourable intrinsic defect type is found to be the cation anti-site defect, in which Li and Mn ions exchange their positions. Lithium ions diffuse via a zig-zag path with very low activation energy of 0.16 eV. Trivalent dopant Sc3+ on Mn site is energetically favourable and could be a synthesis strategy to increase the Li vacancy concentration in Li2MnO2.
Keywords: Defects; Diffusion; Dopants; Atomistic simulation